Association of age and gender among patients undergoing root canal treatment in mandibular first molars - S, HARRITA.; S, PRADEEP; P, SENTHIL MURUGAN (The journal of contemporary issues in business and government, 2021)
Mandibular first molars are the first permanent tooth to develop, they usually have five cusps mesiobuccal, mid-buccal, mesiolingual, distobuccal, and distolingual. International notion of numbering system the right mandible first molar is known as 46 and the left first mandibular Molar are known as 36, they usually have two roots and three canals or sometimes four and also they have four pulp horns usually since they are first to develop they are more prone to decay. Thus the aim of the study is to evaluate the association between age and gender of patients undergoing root canal treatment in a mandibular first molar. A retrospective university setup study where the data were collected from the record management system, where 86000 case sheets were revived and analyzed out of which 609 collected data was compiled and statistically analyzed using SPSS version 23.0. When statistically analyzed on the basis of gender male 47.3% had undergone endodontic treatment in mandibular left first molar (36) and 52.7% had undergone endodontic treatment in mandibular right first molar (46), and in female 42.9% had undergone endodontic treatment in mandibular left first molar (36) and 57.1% and undergone endodontic treatment in mandibular right first molar (46), no significant difference observed (p>0.05). Accordingly when viewed on the basis of age group 18 to 30 years had the maximum number of root canals done in mandibular first molar. The male patients have undergone more endodontic treatment in mandibular first molar compared to female patients, however, no significant difference seen (p>0.05).The mandibular first molars are the first to erupt in the oral cavity and are primary load-bearing teeth during clenching and mastication and in this study, most endodontic treatments were done in patients of younger age group reveals the poor maintenance and poor knowledge of people about the maintenance of the same. Thus it is important to create more awareness about the maintenance of oral hygiene and the use of dental floss to clean interdental areas.